A heat-treated iron-based negative electrode and a cement-based structural battery and a method of preparing the same
Patent Information
- Application Number
- CN202611043689.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]发明目的:本发明的目的在于克服现有技术中水泥基结构电池电极材料活性低、稳定性差、电解质适配性不足及制备流程复杂的缺陷,提供一种热处理铁基负极和水泥基结构电池及其制备方法,实现电池电化学性能、力学性能与稳定性的协同提升,满足建筑结构承载与储能一体化的使用需求
[0036]1. 本发明优化了铁基负极的热处理工艺,通过水热反应和退火处理协同调控铁基负极表面微结构。水热反应使铁基体表面发生适度刻蚀和原位成核,形成均匀分布的前驱体活性位点。退火处理进一步促进前驱体氧化、脱水和晶化,形成与铁基体结合牢固的活性层。该活性层能够增加负极有效反应面积,降低界面电荷转移阻抗,提高导电性、耐腐蚀性和循环稳定性。本申请限定的热处理参数可避免活化不足导致活性位点数量少,也可避免过度反应导致活性层疏松、开裂或脱落,从而在活性位点数量、界面结合强度和结构稳定性之间取得较优平衡,显著提升水泥基结构电池的充放电容量和循环寿命。
Smart Images

Figure CN123017900A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the interdisciplinary field of integrated structural and functional energy storage technology and building materials, specifically involving a heat-treated iron-based negative electrode and a cement-based structural battery and its preparation method. Background Technology
[0002] With the deep integration of the new energy industry and building industrialization, the limitations of traditional buildings that only bear loads are becoming increasingly prominent, making integrated structural energy storage an important development direction in the building sector. Cement-based structural batteries, as a novel energy storage device, combine battery functionality with the load-bearing capacity of cement-based materials. They require no additional building space, effectively reducing the deployment cost of building energy storage systems and possessing broad application prospects. Currently, existing cement-based structural batteries face several technical challenges: First, the negative electrode material has low activity and poor stability, easily forming a passivation layer in the concrete environment, shortening battery life; second, the interfacial contact performance between the electrode material and the cement-based material is poor, resulting in high internal resistance and low charge / discharge capacity; third, the composition ratio of cement-based materials lacks specificity, and the addition of electrolyte is complex, increasing costs and hindering large-scale production. Furthermore, existing cement-based structural battery preparation methods lack systematicity, with poor integration between positive and negative electrode preparation, cement-based material mixing, and casting, leading to insufficient overall structural stability. Simultaneously, the charge / discharge process has not been optimized, failing to match the battery's structural characteristics and electrochemical performance, further affecting energy storage efficiency and cycle life.
[0003] For example, the rechargeable concrete energy storage material and its application provided in CN 116544400 A have not undergone charge and discharge testing, and need to be placed in a liquid-rich environment, which is not conducive to durability requirements and makes it difficult to meet the basic requirements of building structure energy storage.
[0004] Therefore, developing an electrode material with high activity and high stability, and optimizing the preparation process of cement-based structure batteries, has become the key to solving the defects of existing technologies and promoting the industrial application of cement-based structure batteries. Summary of the Invention
[0005] Purpose of the invention: The purpose of this invention is to overcome the defects of low activity, poor stability, insufficient electrolyte compatibility and complex preparation process of cement-based structure battery electrode materials in the prior art, and to provide a heat-treated iron-based negative electrode and cement-based structure battery and its preparation method, so as to achieve synergistic improvement of battery electrochemical performance, mechanical performance and stability, and meet the application requirements of building structure load-bearing and energy storage integration.
[0006] The objective of this invention can be achieved through the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a heat-treated iron-based negative electrode, comprising the following steps: placing iron material in a reaction acid solution for a hydrothermal reaction at a temperature of 100-180 ℃ for 2-12 h; subjecting the product after the hydrothermal reaction to annealing at a temperature of 300-800 ℃ for 0.5-2 h; and obtaining a heat-treated iron-based negative electrode sheet after the reaction is completed.
[0008] The iron material includes at least one of foamed iron, iron mesh, iron sheet, iron foil, iron plate, iron strip, porous iron sheet, sintered porous iron, and iron felt.
[0009] The concentration of the reaction acid solution is 25-100 g / L.
[0010] Wherein, the acid in the reaction acid solution is at least one of carboxylic acid, polycarboxylic acid, and inorganic acid; or, the acid in the reaction acid solution is at least one of oxalic acid, citric acid, acetic acid, formic acid, lactic acid, succinic acid, sulfuric acid, hydrochloric acid, and phosphoric acid.
[0011] Specifically, the heat treatment steps for the negative electrode material include:
[0012] A1: Cleaning and drying treatment, that is, cleaning and drying the iron material: the iron material is cleaned in sequence with anhydrous ethanol, dilute hydrochloric acid and deionized water to remove oil, oxide layer and impurities on the surface of the material. After cleaning, it is placed in a vacuum drying oven to dry to constant weight to ensure the effect of subsequent treatment.
[0013] A2: Tab protection, which means shielding and protecting the tab part on the iron-clad material: using acid-resistant tape, acid-resistant coating, PTFE clamps or other acid-resistant shielding materials on the tab part to prevent the tab from being corroded or damaged during subsequent hydrothermal reactions and cleaning processes, and to ensure the conductivity of the negative electrode.
[0014] A3: Hydrothermal reaction, which involves placing the iron material in a reactive acid solution for a hydrothermal reaction: The reactive acid solution is prepared by selecting at least one of carboxylic acids, polycarboxylic acids, and inorganic acids, preferably at least one of oxalic acid, citric acid, acetic acid, formic acid, lactic acid, succinic acid, sulfuric acid, hydrochloric acid, and phosphoric acid, with a concentration of 25-100 g / L. The cleaned iron material is placed in the reactive acid solution and then placed in a high-temperature, high-pressure reactor for a hydrothermal reaction at a temperature of 100-180℃ for 2-12 hours. During the reaction, the acidic environment performs controlled etching on the iron substrate surface and promotes the in-situ formation of iron salt precursors by dissolved iron ions on the iron material surface, thereby generating uniformly distributed active sites.
[0015] A4: Rinsing and drying, that is, cleaning and drying the product after hydrothermal reaction: After the high temperature and high pressure reactor cools naturally to room temperature, take out the product and rinse it with deionized water and ethanol 2-5 times in sequence to thoroughly remove the residual reaction acid solution and by-products on the surface. After rinsing, dry it to avoid residual impurities affecting the negative electrode performance.
[0016] A5: Annealing treatment, which involves annealing the product to obtain a heat-treated iron-based negative electrode sheet: The washed and dried product is placed in a tube furnace and annealed in an air atmosphere at a temperature of 300-800 ℃ for 0.5-2 h. Annealing treatment promotes the oxidation, dehydration, and crystallization of iron salt precursors, forming an active layer that is firmly bonded to the iron matrix, reducing residual impurities and structural defects, and improving the conductivity, stability, and corrosion resistance of the negative electrode material, ultimately yielding a heat-treated negative electrode sheet.
[0017] Secondly, the present invention provides a negative electrode prepared by the above-described preparation method.
[0018] Thirdly, the present invention provides a cement-based structure battery with a heat-treated iron-based negative electrode, comprising the aforementioned negative electrode, positive electrode and cement-based electrolyte; the negative electrode and positive electrode are symmetrically arranged and cast together with the cement-based electrolyte to form an integrated energy storage device.
[0019] The negative electrode material is a heat-treated iron material; the iron material includes at least one of foamed iron, iron mesh, iron sheet, iron foil, iron plate, iron strip, porous iron sheet, sintered porous iron, and iron felt. Preferably, the iron material is at least one of foamed iron, iron mesh, porous iron sheet, sintered porous iron, or iron felt with a three-dimensional porous structure, so as to improve the contact area and active site utilization rate between the iron-based negative electrode and the cement-based electrolyte.
[0020] The positive electrode includes a conductive substrate and a nickel-based active material supported thereon; the nickel-based active material is selected from at least one of nickel hydroxide, nickel hydroxyl oxide, nickel oxide, and nickel sulfide, and has excellent electrochemical activity and alkali resistance, making it suitable for the alkaline environment of cement-based electrolytes.
[0021] The conductive substrate is at least one of nickel foam, nickel mesh, nickel sheet, stainless steel mesh, or carbon-based conductive material, which has good conductivity and mechanical strength, and can effectively support the nickel-based active material and realize electron transport. The nickel-based active material is loaded onto the surface of the conductive substrate by coating or pressing to ensure uniform loading and tight bonding, and to prevent it from falling off.
[0022] The cement-based electrolyte is composed of cement, polymer, water, and an alkaline compound. The polymer is at least one of PVA and PAM, which can improve the water retention, toughness, and crack resistance of the cement-based electrolyte, regulate the internal pore and liquid phase distribution, and maintain a continuous and stable ion transport channel. The alkali is at least one of KOH, NaOH, or Ca(OH)2, which can adjust the alkaline environment of the electrolyte, improve the ionic conductivity, and adapt to the electrochemical reactions of the positive and negative electrodes. The synergistic effect of the components ensures that the cement-based electrolyte has sufficient mechanical strength to meet the load-bearing requirements of the building structure, and also achieves efficient ion transport to ensure the charging and discharging performance of the battery.
[0023] Fourthly, the present invention also provides a method for preparing the above-mentioned cement-based structure battery with a heat-treated iron-based negative electrode, which is used to prepare the above-mentioned cement-based structure battery, comprising the following steps:
[0024] (a) Preparation of heat-treated iron-based negative electrode;
[0025] (b) A positive electrode is obtained by loading a nickel-based active material onto a conductive substrate;
[0026] (c) A cement-based electrolyte is obtained by mixing cement, polymer, water and alkaline compound;
[0027] (d) Arrange the negative and positive electrodes symmetrically, pour cement-based electrolyte and solidify to obtain a cement-based structure battery.
[0028] Specifically, the preparation method of cement-based structured batteries includes the following steps:
[0029] (a) Preparation of heat-treated iron-based negative electrode: using iron material as raw material, performing the heat treatment steps A1-A5 above, to obtain heat-treated negative electrode sheet;
[0030] (b) Preparation of positive electrode: Select the corresponding type of conductive substrate, and load the nickel-based active material onto the surface of the conductive substrate by coating or pressing to obtain the positive electrode sheet;
[0031] (c) Preparation of cement-based electrolyte: Mix cement, polymer, water and alkaline compound, stir evenly to form a paste-like cement-based electrolyte, ensuring the uniformity and fluidity of the electrolyte, which is convenient for casting and molding;
[0032] (d) Molding and curing: The prepared heat-treated negative electrode and positive electrode are symmetrically arranged and placed in a preset mold. The above-mentioned cement-based electrolyte is poured in. After the electrolyte is cured, a cement-based structure battery is obtained.
[0033] The present invention also provides the charging and discharging steps of the above-mentioned cement-based structure battery. A single charging and discharging process includes: first, charging at a constant current density of 0.5-10.0 mA / cm2 until the voltage is 1.8-2.0 V, and then maintaining the voltage for 0.5-5 h to ensure that the battery is fully charged; after charging is completed, constant current discharge is performed to adapt to the structural characteristics and electrochemical performance of the battery and extend the cycle life of the battery.
[0034] In this invention, after an acidic hydrothermal reaction, the iron substrate surface undergoes controlled etching, increasing surface roughness and specific surface area, and generating iron-containing precursor active sites in situ on the iron substrate surface. Subsequently, annealing treatment causes the precursor to oxidize, dehydrate, and crystallize, forming a firmly bonded iron oxide active layer with the iron substrate. This active layer weakens the resistance of the dense passivation layer to the iron substrate reaction, increases the effective reaction area of the negative electrode, and improves electron transport and interfacial charge transfer processes, thereby enhancing the electrochemical activity and cycle stability of the iron-based negative electrode in a cement-based alkaline environment.
[0035] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0036] 1. This invention optimizes the heat treatment process of iron-based anodes by synergistically regulating the surface microstructure of the iron-based anode through hydrothermal reaction and annealing. The hydrothermal reaction causes moderate etching and in-situ nucleation on the iron substrate surface, forming uniformly distributed precursor active sites. Annealing further promotes precursor oxidation, dehydration, and crystallization, forming an active layer firmly bonded to the iron substrate. This active layer increases the effective reaction area of the anode, reduces interfacial charge transfer impedance, and improves conductivity, corrosion resistance, and cycle stability. The heat treatment parameters specified in this application avoid insufficient activation leading to a small number of active sites, and also avoid excessive reaction leading to a loose, cracked, or detached active layer, thus achieving a better balance between the number of active sites, interfacial bonding strength, and structural stability, significantly improving the charge-discharge capacity and cycle life of cement-based structure batteries.
[0037] 2. The iron-based materials used in this invention are widely available and cost-controllable, facilitating large-scale production. Furthermore, the preparation process is convenient and requires no complex equipment. This further increases the contact area between the negative electrode and the cement-based electrolyte, balancing the battery's energy storage performance and structural load-bearing capacity.
[0038] 3. This invention optimizes the charging and discharging process, matches the battery structure and electrochemical performance, and further improves the battery's energy storage efficiency and stability. Attached Figure Description
[0039] Figure 1 These are microscopic images of the iron anode before and after heat treatment in Example 1.
[0040] Figure 2The cycling performance curve of the cement-based structured battery prepared in Example 1 is shown.
[0041] Figure 3 The cycling performance curve of the cement-based structured battery prepared in Example 2 is shown.
[0042] Figure 4 The cycling performance curve of the cement-based structured battery prepared in Example 3 is shown.
[0043] Figure 5 The cycling performance curve of the cement-based structured battery prepared in Example 4 is shown.
[0044] Figure 6 The cycling performance curve of the cement-based structured battery prepared in Example 5 is shown.
[0045] Figure 7 The cycling performance curves of the cement-based structured battery prepared in Example 6 are shown.
[0046] Figure 8 The cycling performance curve of the cement-based structured battery prepared in Example 7 is shown.
[0047] Figure 9 The cycling performance curve of the cement-based structured battery prepared in Example 8.
[0048] Figure 10 The cycling performance curve of the cement-based structured battery prepared in Example 9.
[0049] Figure 11 The cycling performance curve of the cement-based structured battery prepared in Example 10 is shown.
[0050] Figure 12 The cycling performance curve of the cement-based structured battery prepared in Example 11 is shown.
[0051] Figure 13 The cycling performance curve of the cement-based structured battery prepared in Example 12 is shown.
[0052] Figure 14 The cycling performance curve of the cement-based structured battery prepared in Example 13 is shown.
[0053] Figure 15 The cycling performance curve of the cement-based structured battery prepared in Example 14 is shown.
[0054] Figure 16 The cycling performance curve of the cement-based structured battery prepared in Example 15 is shown.
[0055] Figure 17 Cyclic performance curves of the cement-based structured battery prepared for Comparative Example 1.
[0056] Figure 18Cyclic performance curves of the cement-based structured battery prepared for Comparative Example 2.
[0057] Figure 19 Cyclic performance curves of the cement-based structured battery prepared for Comparative Example 3. Detailed Implementation
[0058] The present invention will be further described in detail below with reference to specific embodiments, but the implementation of the present invention is not limited thereto.
[0059] The cement used in the following examples is P·O 42.5 ordinary Portland cement.
[0060] Example 1:
[0061] A cement-based structured battery with a heat-treated iron-based negative electrode, the preparation method of which includes the following steps:
[0062] (a) Preparation of heat-treated iron-based negative electrode: Foamed iron was selected as the raw material, with a specific surface area of 50 m². 2 / g, with a thickness of 0.5mm, a purity of ≥99.5%, and an integrated structure containing tabs;
[0063] A1: The foamed iron was ultrasonically cleaned sequentially with anhydrous ethanol, dilute hydrochloric acid, and deionized water, and then dried in a vacuum drying oven to constant weight; A2: The tab portion of the foamed iron was wrapped with acid-resistant tape; A3: An oxalic acid solution with a concentration of 50 g / L was prepared as the reaction acid solution. The cleaned foamed iron was placed in the oxalic acid solution and then placed in a high-temperature and high-pressure reactor for hydrothermal reaction at 150 ℃ for 6 h; A4: After naturally cooling to room temperature, it was rinsed with deionized water and ethanol, and then dried in a vacuum drying oven at 60 ℃ for 2 h; A5: The dried foamed iron was placed in a tube furnace and annealed at 400 ℃ in air atmosphere for 1 h to obtain the heat-treated foamed iron negative electrode;
[0064] (b) Preparation of positive electrode: Nickel foam was selected as the conductive substrate with a thickness of 1 mm. Nickel hydroxide was loaded onto the surface of the nickel foam by coating to obtain the positive electrode sheet.
[0065] (c) Preparation of cement-based electrolyte: Cement:PVA1799:water:KOH = 100:8:40:4 by mass and stir evenly;
[0066] (d) Molding and curing: Heat-treated foamed iron negative electrode and positive electrode are symmetrically arranged with a spacing of 4 mm, placed in a mold and the above-mentioned cement-based electrolyte is poured. After curing for 1 day, the mold is removed and cured for 28 days to obtain a cement-based structure battery.
[0067] Charge / discharge steps: First, at 3.0 mA / cm 2Charge at a constant current to 1.9 V, maintain this voltage for 2 hours, and then discharge at a constant current.
[0068] Example 2:
[0069] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the hydrothermal reaction temperature in A3 is 100 °C, while the remaining steps and parameters are the same as in Example 1.
[0070] Example 3:
[0071] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the hydrothermal reaction temperature in A3 is 180 °C, while the remaining steps and parameters are the same as in Example 1.
[0072] Example 4:
[0073] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the hydrothermal reaction time in A3 is 2 h, while the remaining steps and parameters are the same as in Example 1.
[0074] Example 5:
[0075] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the hydrothermal reaction time in A3 is 12 h, while the remaining steps and parameters are the same as in Example 1.
[0076] Example 6:
[0077] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the annealing temperature in A5 is 300 °C, while the remaining steps and parameters are the same as in Example 1.
[0078] Example 7:
[0079] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the annealing temperature in A5 is 800 °C, while the remaining steps and parameters are the same as in Example 1.
[0080] Example 8:
[0081] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the annealing time in A5 is 0.5 h, while the remaining steps and parameters are the same as in Example 1.
[0082] Example 9:
[0083] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the annealing time in A5 is 2 h, while the remaining steps and parameters are the same as in Example 1.
[0084] Example 10:
[0085] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the solution concentration in A3 is 25 g / L, while the remaining steps and parameters are the same as in Example 1.
[0086] Example 11:
[0087] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the solution concentration in A3 is 100 g / L, while the remaining steps and parameters are the same as in Example 1.
[0088] Example 12:
[0089] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the reaction acid solution in A3 is a citric acid solution, while the remaining steps and parameters are the same as in Example 1.
[0090] Example 13:
[0091] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the reaction acid solution in A3 is an acetic acid solution, while the remaining steps and parameters are the same as in Example 1.
[0092] Example 14:
[0093] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a way that differs from that in Example 1 in that: in step (c) when preparing the cement-based electrolyte, PVA and KOH are not added, but only the cement and water are mixed at a mass ratio of 100:40. The remaining steps and parameters are the same as in Example 1.
[0094] Example 15:
[0095] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the charge-discharge step does not include a 2-hour constant voltage charging period; instead, it is directly charged at 3.0 mA / cm². 2 After constant current charging to 1.9 V, constant current discharge is performed.
[0096] The following comparative examples are set up to compare with the embodiments of the present invention, further illustrating the technical advantages of the present invention. Except for the specified differences, the other steps and parameters of each comparative example are the same as those of Example 1.
[0097] Comparative Example 1:
[0098] A cement-based structure battery, the preparation method of which differs from that of Example 1 is as follows: when preparing the iron-based negative electrode in step (a), the heat treatment steps A1-A5 are not performed, and untreated foamed iron is directly selected as the negative electrode. The remaining steps and parameters are the same as those in Example 1.
[0099] Comparative Example 2:
[0100] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the reaction temperature in A3 is 80°C, while the remaining steps and parameters are the same as in Example 1.
[0101] Comparative Example 3:
[0102] A cement-based structure battery with a heat-treated iron-based negative electrode is prepared in a manner that differs from that of Example 1 in that the temperature in A5 is 200°C, while the remaining steps and parameters are the same as in Example 1.
[0103] Performance testing
[0104] The iron anode before and after heat treatment was observed using a scanning electron microscope to compare the changes in surface morphology and active structure. Figure 1 The results show that after heat treatment, a plate-like or granular active structure is formed on the surface of the iron anode, indicating that hydrothermal reaction and annealing can increase the active sites.
[0105] The cycle performance of the cement-based battery structure was tested using a constant current-constant voltage charge / constant current discharge method. Unless otherwise specified, the battery was first charged to the set voltage using the current density described in each embodiment, then held at constant voltage for the corresponding time, followed by constant current discharge. The discharge capacity was normalized to the areal capacity based on the electrode geometry, and the unit is mAh / cm². 2 .
[0106] The mechanical properties of cement-based structural batteries were tested using a universal testing machine, with six samples tested in each group.
[0107] Table 1 Performance Comparison of Various Embodiments and Comparative Solutions
[0108] Example 1 2.14 26.3 Example 2 1.28 26.3 Example 3 1.66 26.3 Example 4 1.34 26.3 Example 5 1.53 26.3 Example 6 1.74 26.3 Example 7 1.60 26.3 Example 8 1.45 26.3 Example 9 1.92 26.3 Example 10 1.5 26.3 Example 11 1.68 26.3 Example 12 1.94 26.3 Example 13 1.89 26.3 Example 14 1.30 27.4 Example 15 0.96 26.3 Comparative Example 1 0.01 26.3 Comparative Example 2 0.03 26.3 Comparative Example 3 0.04 26.3
[0109] Table 1 shows the specific capacity and compressive strength of the cement-based structural batteries prepared in Examples 1-15 and Comparative Examples 1-3. Figure 2-19 The charge-discharge cycle curves of the cement-based structure batteries prepared in Examples 1-15 and Comparative Examples 1-3 are shown respectively. These indicate that heat treatment improves the electrochemical performance of the full cell; the addition of polymers reduces the internal resistance of the cement-based material and increases the areal capacity; and optimization of the charge-discharge regime, using constant voltage charging, significantly improves the areal capacity of the cement-based structure batteries.
[0110] As hydrothermal temperature and time increase, the specific capacity of cement-based structure batteries first increases and then decreases. This indicates that when the hydrothermal temperature is too low or the time is too short, the etching and in-situ nucleation of the iron substrate surface are insufficient, resulting in a limited number of active sites. When the hydrothermal temperature is too high or the time is too long, the surface reaction is excessive, which can easily lead to a loose precursor structure or decreased interfacial bonding stability. As the annealing temperature and time increase, the specific capacity of cement-based structure batteries first increases and then decreases. This indicates that when the annealing temperature is too low or the time is too short, the oxidation, dehydration, and crystallization of the precursor are insufficient, resulting in insufficient crystallinity and stability of the active layer. When the annealing temperature is too high or the time is too long, it may cause sintering, coarsening, or excessive oxidation of the active layer, reducing the effective reaction area and interfacial transport efficiency. Appropriate heat treatment temperature and time effectively improve the performance of cement-based structure batteries.
[0111] As can be seen from the performance of the embodiments, this application effectively improves the problems of low activity, poor stability and insufficient electrode adaptability of existing cement-based structure batteries by controlling the microstructure of the iron-based negative electrode surface through heat treatment. It realizes the integration of building load-bearing and energy storage functions, and has the advantages of convenient preparation, controllable cost and good stability. It can be widely used in self-powered buildings, energy storage infrastructure and other fields.
[0112] Meanwhile, the performance of Comparative Example 1 shows that the performance of batteries with iron-based anodes that have not undergone the heat treatment process of this application is significantly reduced. This is because this application synergistically regulates the surface microstructure of the iron-based anode through hydrothermal reaction and annealing. The hydrothermal reaction causes moderate etching and in-situ nucleation on the iron substrate surface, forming uniformly distributed precursor active sites. Annealing further promotes precursor oxidation, dehydration, and crystallization, forming an active layer firmly bonded to the iron substrate. This active layer increases the effective reaction area of the anode, reduces interfacial charge transfer impedance, and improves conductivity, corrosion resistance, and cycle stability.
[0113] In the heat treatment process, analysis of the performance of Comparative Examples 2 and 3 reveals that the heat treatment process parameters have a significant impact on the final battery performance. This is because the heat treatment process parameters affect the performance of the final active layer. Specifically, Comparative Example 2 suffers from insufficient etching and in-situ nucleation on the iron substrate surface, while Comparative Example 3 suffers from insufficient annealing temperature, resulting in low crystallinity of the surface precursor and weak bonding between the active layer and the substrate, leading to poor performance of the cement-based structure battery. Therefore, only by preparing the battery under appropriate heat treatment process parameters can a better balance be achieved between the number of active sites, interfacial bonding strength, and structural stability, significantly improving the charge / discharge capacity and cycle life of the cement-based structure battery. In Example 14, the poor ion transport capacity in the cement-based electrolyte leads to increased internal resistance of the structure battery. In Example 15, insufficient electrode activation and incomplete participation of active materials in the reaction result in low discharge capacity of the structure battery.
[0114] The above detailed description of the embodiments is intended to facilitate understanding and use of the present invention by those skilled in the art. Those skilled in the art can easily modify these embodiments and apply the general principles therein to other embodiments without creative effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention are all within the protection scope of the present invention.
Claims
1. A method for preparing a heat-treated iron-based negative electrode, characterized in that, The process includes the following steps: placing iron material in a reaction acid solution for hydrothermal reaction at a temperature of 100-180 ℃ for 2-12 h; annealing the product after hydrothermal reaction at a temperature of 300-800 ℃ for 0.5-2 h; and finally, obtaining a heat-treated iron-based negative electrode sheet.
2. The method for preparing a heat-treated iron-based negative electrode according to claim 1, characterized in that, The iron material includes at least one of foamed iron, iron mesh, iron sheet, iron foil, iron plate, iron strip, porous iron sheet, sintered porous iron, and iron felt.
3. The method for preparing a heat-treated iron-based negative electrode according to claim 1, characterized in that, The concentration of the reaction acid solution is 25-100 g / L.
4. The method for preparing a heat-treated iron-based negative electrode according to claim 1, characterized in that, The acid in the reaction acid solution is at least one of carboxylic acids, polycarboxylic acids, and inorganic acids; or, the acid in the reaction acid solution is at least one of oxalic acid, citric acid, acetic acid, formic acid, lactic acid, succinic acid, sulfuric acid, hydrochloric acid, and phosphoric acid.
5. A negative electrode prepared by the preparation method according to any one of claims 1-4.
6. A cement-based structural battery, characterized in that, The battery comprises the negative electrode, positive electrode, and cement-based electrolyte as described in claim 5.
7. A cement-based structural battery according to claim 6, characterized in that, The positive electrode includes a conductive substrate and a positive electrode material loaded on the conductive substrate. The positive electrode material is a nickel-based active material selected from at least one of nickel hydroxide, nickel hydroxyl oxide, nickel oxide, and nickel sulfide. The conductive substrate is at least one of nickel foam, nickel mesh, nickel sheet, stainless steel mesh, or carbon-based conductive material.
8. The cement-based structural battery according to claim 7, characterized in that, The cement-based electrolyte is composed of cement, polymer, water and alkaline compound, wherein the polymer is at least one of PVA and PAM; and the alkaline compound is at least one of KOH, NaOH and Ca(OH)2.
9. A method for preparing a cement-based structural battery according to claim 7, characterized in that, Includes the following steps: (a) Preparation of heat-treated iron-based negative electrode; (b) A positive electrode is obtained by loading a nickel-based active material onto a conductive substrate; (c) A cement-based electrolyte is obtained by mixing cement, polymer, water and alkaline compound; (d) Arrange the negative and positive electrodes symmetrically, pour cement-based electrolyte and solidify to obtain a cement-based structure battery.
10. The method for preparing a cement-based structural battery according to claim 9, characterized in that, The fabrication process of the cement-based structure battery also includes a charge-discharge step, specifically: first, charging at 0.5-10.0 mA cm⁻¹ -2 Charge at a constant current until the voltage reaches 1.8-2.0 V, then maintain the voltage for 0.5-5 hours, followed by constant current discharge.
Citation Information
Patent Citations
Rechargeable concrete energy storage material and application thereof
CN116544400A